A questionnaire survey study of the building industry’s attitude towards social sustainability in Sweden and Chin - Zhang, Jingxuan (My University, 2017)
In today’s construction industry, there are much research and studies on environmental and economic sustainability, but the topic of social sustainability often lacks attention. The concept of social sustainability covers a large area, and it is hard to define. This thesis has studied different frameworks of social sustainability and has provided measurable criteria of social sustainability. The criteria were used to analyse the building industry’s current attitude towards social sustainability development in Sweden and China. In other words, this thesis tried to find out social related problems that the construction industry is facing, and the measures that the industry has taken to reduce the impact of social problems. Since the thesis studied a large-range topic in a large industry, a quantitative method was used in this thesis. Survey questionnaires regarding social sustainability development were sent out to companies in the construction industry in Sweden and China. The companies included architecture firms, consultant companies, contractors and real estate companies. The questionnaires were sent out by Survey Monkey, and the answers were analyzed by using an Excel spreadsheet. The results showed that in both Sweden and China, companies had personnel that were dealing with social sustainability related issues. However, the Swedish construction industry and the Chinese construction industry perceived that the face different social sustainability related issues. The companies in Sweden and China took different measures to reduce the social impacts. The results of the thesis can be used as a benchmark for future development of social sustainability in both countries. Because the society of China and Sweden are different, the results from the two nations were not meant to be compared or use one as a benchmark for another one.
Keywords: Annan samhällsvetenskap; Other Social Sciences